Arid and semi-arid geomorphology - Goudie, Andrew S. (Cambridge : Cambridge University Press, 2013)
"Global analysis of landforms of deserts and the processes that mould them, for advanced students and researchers"--
"Based on four decades of research by Professor Andrew Goudie, this volume provides a state-of-the-art synthesis of our understanding of desert geomorphology. It presents a truly international perspective, with examples from all over the world. Extensively referenced and illustrated, it covers such topics as the importance of past climatic changes, the variability of different desert environments, rock breakdown, wind erosion and dust storm generation, sand dunes, fluvial and slope forms and processes, the role of the applied geomorphologist in desert development and conservation, and the Earth as an analogue for other planetary bodies. This book is destined to become the classic volume on arid and semi-arid geomorphology for advanced students and researchers in physical geography, geomorphology, Earth science, sedimentology, environmental science, and archaeology"--
Machine generated contents note: 1. Introduction; 2. Rock weathering and desert surfaces; 3. Aeolian geomorphology; 4. Dunes; 5. Rivers and slopes; 6. Applied geomorphology in deserts: hazards, resources and the future; 7. Regional variety.
Includes bibliographical references (pages 325-447) and index.
Keywords: Geomorphology; Deserts; Arid regions; Earth Sciences; Geography